Architectural styles of Malaysian mosque: suitability in compact urban settings - Asif, Nayeem; Utaberta, Nangkula; Sarram, Arman (Universiti Teknologi MARA, 2019)
The concept of urban mosque stems from more extensive reasons that mostly come from the overall issues of industrialization. Considering the challenges related to rapid urban growth, public institutions, such as mosque and its compatibility is required to be assessed in the context of compact cities. This study therefore aim to evaluate the planning and layout of six different styles of mosque in Malaysia in terms of their suitability in compact urban settings. Due to its genre, the study adopts case study as a qualitative research strategy as its research method. Content analysis is conducted on the compiled literatures to give indication on the expected outcome. Following a brief comparative discussion, this paper shows that, mosque with modern architectural style among all six typologies is most suitable in the context of compact urban settings. Factors considered for the evaluation of mosques include layout progression of the mosque whether horizontal or vertical, provision for vertical stacking of spaces, symmetry in topology as well as in elevation and space types in terms of flexible usage. Scope of this paper is limited to the assessment of literatures only, which opens the window for further in-depth study on actual case studies related to this topic.